2021
DOI: 10.1002/hed.26787
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of ipsilateral central lymph node metastasis for contralateral central lymph node metastasis in patients with thyroid cancer: Systematic review and meta‐analysis

Abstract: Careful consideration of prophylactic central compartment dissection is required to ensure that its benefits outweigh its risks in the thyroid cancer. Sixteen prospective or retrospective studies were included. True positive, true negative, false positive, and false negative were extracted from each study. The diagnostic odds ratio of ipsilateral central lymph node metastasis (iCLNM) for predicting contralateral central lymph node metastasis (cCLNM) was 12.9237 (95% confidence interval [CI], 8.1595–20.4695). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…This was suggested also in a previous similar metaanalyses study which showed similar promising outcomes for prophylactic central neck dissection following total thyroidectomy in improving the haemorrhage and reducing the surgical site wound infection. [56][57][58][59] Well-conducted randomised controlled trials are needed to assess these factors and the combination of different ages, ethnicity, and other variants of subjects; because our meta-analysis study could not answer whether different ages, ethnicity, and gender are related to the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was suggested also in a previous similar metaanalyses study which showed similar promising outcomes for prophylactic central neck dissection following total thyroidectomy in improving the haemorrhage and reducing the surgical site wound infection. [56][57][58][59] Well-conducted randomised controlled trials are needed to assess these factors and the combination of different ages, ethnicity, and other variants of subjects; because our meta-analysis study could not answer whether different ages, ethnicity, and gender are related to the results.…”
Section: Discussionmentioning
confidence: 99%
“…This was suggested also in a previous similar meta‐analyses study which showed similar promising outcomes for prophylactic central neck dissection following total thyroidectomy in improving the haemorrhage and reducing the surgical site wound infection. 56 , 57 , 58 , 59 …”
Section: Discussionmentioning
confidence: 99%
“…Kim et al suggested that ipsilateral central lymphatic metastasis could predict contralateral central lymphatic metastasis. In addition, they demonstrated a strong association between contralateral central lymphatic metastasis and speci c clinicopathological features, including young male, multifocality, external thyroid extension and tumor size [27].However, for patients of PTC with CN1b, total thyroidectomy plus lateral cervical lymph node dissection is generally performed. Few studies have reported whether the contralateral central lymph node dissection is necessary for patients with unilateral PTC with N1b.In our study, patients with ipsilateral central lymphatic metastasis rate is 78.2.…”
Section: Discussionmentioning
confidence: 99%
“…Regional lymph node metastases develop in 20-90% of patients with PTC, with the cervical central compartment, or level VI node, being the primary zone of lymphatic involvement (5).…”
Section: Introductionmentioning
confidence: 99%